Stent-Assisted Coiling in Acutely Ruptured Intracranial Aneurysms: A Qualitative, Systematic Review of the Literature - Bodily, K.D.; Cloft, H.J.; Lanzino, G.; Fiorella, D.J.; White, P.M.; Kallmes, D.F. (American Journal of Neuroradiology, 2011)
BACKGROUND AND PURPOSE: The use of stents for treatment of morphologically unfavorable, acutely ruptured aneurysms is avoided by most operators because of concerns about the risk of using dual antiplatelet therapy in the setting of acute SAH. Our aim was to review the literature regarding stent-assisted coil embolization of acutely ruptured intracranial aneurysms to determine the safety and efficacy of this treatment option. MATERIALS AND METHODS: Articles including ≥5 patients with ruptured aneurysms who were treated acutely with stent-assisted coiling or uncovered stent placement alone were identified. Data on clinical presentation, technical success, surgical crossover, intracranial complications, and clinical outcome were evaluated. RESULTS: A total of 17 articles were identified reporting 339 patients who met inclusion criteria. Among 212 patients with available data, technical success was noted in 198 (93%) patients. Three hundred twenty-six (96%) of 339 patients received both heparin during the procedure and dual-antiplatelet therapy during or immediately postprocedure. One hundred thirty (63%) of 207 aneurysms were completely occluded. Six (2%) of 339 patients required surgical crossover, usually for failure in stent placement or for intraprocedural aneurysm rupture. Clinically significant intracranial hemorrhagic complications occurred in 27 (8%) of 339 patients, including 9 (10%) of 90 patients known to have EVDs who had ventricular drain−related hemorrhages. Clinically significant thromboembolic events occurred in 16 (6%) of 288 patients. Sixty-seven percent of patients had favorable clinical outcomes, 14% had poor outcomes, and 19% died. CONCLUSIONS: Stent-assisted coiling in ruptured aneurysms can be performed with high degrees of technical success, but adverse events appear more common and clinical outcomes are likely worse than those achieved without stent assistance. Thromboembolic complications appear reasonably well-controlled. Reported EVD-related hemorrhagic complications were uncommon, though the total number of EVDs placed was unknown. EVDexternal ventricular drainGOSGlasgow Outcome ScoreHHHunt and HessmRSmodified Rankin ScoreSAHsubarachnoid hemorrhage